KAJIAN P-TERSEDIA PADA TANAH SAWAH SULFAT MASAM POTENSIAL - Achmad Hambali Nasution; Fauzi Fauzi; Lahuddin Musa (Universitas Sumatera Utara, 2014)
The research was conducted to examine P-available of paddy soil potential of acid sulfate withBray II, Truog and Olsen. The research held in Seed Technology Laboratory (seeding), green houseand also in Research and Technology Laboratory Agriculture Faculty University of SumateraUtara. The research used non factorial Randomized Block Design with 3 repetition, which as mainfactor is the giving of Natural Phosphate with 9 kind of dosages, that is: 0, 50, 100, 150, 200, 250,300, 350, and 400 ppm. The giving of Natural Phosphate was significant to the phosphorus sorptionwith the best dosage is P7 (350 ppm) and pH with the best dosage is P8 (400 ppm). The examiningof P-available from the giving of natural phosphate results that the value of P-available by usingBray II and Truog method was higher than the value of P-available by using Olsen method, andthere is no appropriate value of P critical limit for each method.Keywords: P-Available, acid sulfate soil, potential